Development of a PCR assay to detect the potential production of nivalenol in Fusarium poae - Dinolfo, María Inés (2012)
Fusariumspecies can produce mycotoxins, which can contaminate cereal-based food producing adverse effects for human and animal health. In recent years, the importance ofFusarium poaehas increased within theFusariumhead blight complex.Fusarium poaeis known to produce trichothecenes, especially nivalenol, a potent mycotoxin able to cause a variety of toxic effects. In this study, a specific primer pair was designed based on thetri7gene to detect potential nivalenol-producingF. poaeisolates. A total of 125F. poae, fourF. cerealis, twoF. culmorum, oneF. langsethiae, oneF. sporotrichioidesand sevenF. graminearum, plusF. austroamericanum, F. meridionale, F. graminearum sensu strictoandF. cortaderiaefrom the NRRL collection were analysed, and onlyF. poaeisolates gave a positive result for the presence of a 296-bp partialtri7DNA fragment. Moreover, the primer set was tested from cereal seed samples whereF. poaeand otherFusariumspecies with a negative result for the specific reaction (F. graminearum, F. oxysporum, F. chlamydosporum, F. sporotrichioides, F. equisetiandF. acuminatum) were isolated, and the expected fragment was amplified. We developed a rapid and reliable PCR assay to detect potential nivalenol-producingF. poaeisolates.